The detection of Simian virus 40 in mesotheliomas from New Zealand and England using real time FRET probe PCR protocols. Issue 10 (26th September 2003) - Mayall, F; Barratt, K; Shanks, J
Abstract : Aims: To detect Simian virus 40 (SV40) DNA in mesotheliomas from New Zealand and from England using novel real time FRET probe polymerase chain reaction (PCR) protocols. Methods: Twenty four mesotheliomas from New Zealand (Central North Island) and 32 mesotheliomas from England (Greater Manchester region) were examined. Two real time FRET probe PCR protocols were optimised and their analytical sensitivity compared using dilutions of SV40 DNA. A conventional SV40 large tumour antigen protocol with detection by probe hybridisation and chemiluminescent Southern blotting was also optimised. Results: Both real time PCR protocols had the same analytical sensitivity, detecting down to 10 −6 pg of SV40 DNA for each reaction, approximately one SV40 copy. All of the 56 mesothelioma samples contained amplifiable β globin DNA, but none contained amplifiable SV40 DNA with the conventional large T antigen PCR–Southern blotting protocol, or the two real time FRET probe PCR protocols. The positive and negative controls gave the expected results. There was no evidence of inhibition. Conclusions: There is abundant evidence in the literature for the presence of SV40 in mesotheliomas. However, this study found no evidence of SV40 in mesotheliomas from England and New Zealand. The extensive use of SV40 contaminated polio vaccine in New Zealand does not seem to have resulted in SV40 associated mesotheliomas.